The Discrete Process of Storage with Two Priority Classes - Julius Rebo (Communications - Scientific letters of the University of Zilina, 2000)
This paper is devoted to a specific model of the discrete process of storage with two priority classes. Every priority class of the elements is formed by independent Poisson distributed incoming streams of the elements. There are derived some basic characteristic values, a method of assignment optimal out-going capacities for the classes of priority and a costs minimising method for the length of the storage period as well.